Fascination for and Rewriting of the Nota Roja in Hurricane Season (2017) by Fernanda Melchor - Vázquez Soriano, Michelle (2023)
Fernanda Melchor (Mexico, 1982) gained international fame with the publication of her novel Hurricane Season (2017), a fictional story inspired by the nota roja, the name given to the crime news in the Mexican press. As a journalist, Melchor has always claimed the impossibility of journalistic objectivism. However, she acknowledges that the fictional treatment of her novel was imposed on her by the context of extreme violence that exists in Veracruz, her home state. The objective of this work is to analyse the mechanisms that the author takes up both from Latin American alternative crime fiction (thesis developed by the writer Diego Trelles Paz, 2017), as well as from new journalism to offer us a possible story where drug trafficking and corruption have created inaccessible areas. Finally, we reflect on the fascination exerted by the nota roja in her writing: a fascination that works sometimes as a social criticism of impunity and, other times, as a mirror of our darkest impulses.